Study guide: HDPS3603 early science for children - Badzis, Mastura (Centre for Instructional Design & Technology, Open University Malaysia, 2012)
This course is designed to educate learners on the rationale and importance of learning science among young children. The learners will be familiarised to some basic scientific knowledge and scientific sills for teaching science to young children. The learners will have the opportunity to set up play-based sciences activities using various teaching strategies as well as provide a conducive environment for learning science in the early childhood setting.